Increased Asynchronous Release and Aberrant Calcium Channel Activation in Amyloid Precursor Protein Deficient Neuromuscular Synapses - Yang, Li (2007)
Despite the critical roles of the amyloid precursor protein (APP) in Alzheimer's disease pathogenesis, its physiological function remains poorly established. Our previous studies implicated a structural and functional activity of the APP family of proteins in the developing neuromuscular junction (NMJ). Here we performed comprehensive analyses of neurotransmission in mature neuromuscular synapse of APP deficient mice. We found that APP deletion led to reduced paired-pulse facilitation and increased depression of synaptic transmission with repetitive stimulation. Readily releasable pool size and total releasable vesicles were not affected, but probability of release was significantly increased. Strikingly, the amount of asynchronous release, a measure sensitive to presynaptic calcium concentration, was dramatically increased, and pharmacological studies revealed that it was attributed to aberrant activation of N- and L-type Ca(2+) channels. We propose that APP modulates synaptic transmission at the NMJ by ensuring proper Ca(2+) channel function.